Daily field checking list by Walter Rosene, August 11, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated August 11, 1936. This checklist was used by Walter Rosene to record birds sighted around McGregor Heights with Tom Scott and a group of people between 5:30 and 8:30. Plustek--flatbed